Influence of composition on the structural-phase state, electrophysical and magnetotransport properties of alloy thin films based on Co and Cu. (May 2021) - Shpetnyi, I.O.; Protsenko, I.Yu; Vorobiov, S.I.; Grebinaha, V.I.; Satrapinskyy, L.; Luciński, T.
Abstract: The influence of the composition of alloy thin films based on Co and Cu on their structural-phase state, electrophysical and magnetotransport properties is presented. The studies were performed for non-annealed and annealed (up to T max = 800 K) alloy thin films based on Co and Cu with a thickness of 40 nm, in a wide range of cobalt atomic fractions (0.20 ≤ x ≤ 0.75). For alloy thin films with x ≤ 0.42, thermal treatment in the temperature range from 300 to 800 K for 30 min caused an increase in the value of the giant magnetoresistance (GMR) and coercivity due to the increase in the size of the hcp-Co granules. The highest amplitude of GMR were found in alloys thin films with a total atomic fraction of Co at x = 0.32. The calculation of the thermal coefficient of resistance of alloys showed a qualitative agreement with experiment results for alloy thin films with a total atomic fraction Co x ≤ 0.32. Highlights: The influence of the composition of granular films on the electrophysical and MR properties were studied. The annealing leads to increase the values of magnetoresistance and coercive force. At a concentration of x Co ≥ 0.75 an anisotropic magnetoresistance has observed. The maximum value of GMR has observed after annealing at the x Co = 0.32.